Computational studies on the effects of a central shaft and a guiding wall on the savonius hydrokinetic turbine performances - Tantichukiad, Komsan; Yahya, Azmi; Mohd Mustafah, Anas; Harith, Hazreen Haizi; Mohd Rafie, Azmin Shakrine; Mat Su, Ahmad Suhaizi (HH Publisher, 2021)
Most wetland rice production schemes have good networks of irrigation and drainage canals built for the benefit of the farmers to perform farming activities. The canals have ample volume of running water all year round and could be harnessed for hydropower. The Savonius hydrokinetic turbine has been generally used to generate electrical energy as the means of renewable source over fossil fuels. Numerous parameters have been studied to enhance the performance of the turbine. However, the turbine power performance is still low as compared to other types even though it is known to have excellent torque characteristics. Therefore, the objectives of this study are to evaluate the effects of a central shaft and a guiding wall on the performances of the Savonius hydrokinetic turbines by using two-dimensional computational simulations. ANSYS Fluent software with the standard k-ε turbulence model and dynamic mesh motion techniques were used to get the optimum central shaft and guiding wall configurations. The central shaft was studied in three cases; (I) with a full shaft, (II) with a shaft and space, and (III) without shaft between two end plates. Moreover, the turbine performances were also evaluated with and without the presence of a guiding wall. The turbine performances were computed. Simulation results e.g. velocity, pressure contours and flow structures across a SHKT model were analysed and discussed.